2003
DOI: 10.1046/j.1365-2133.2003.05243.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of SPINK5 gene polymorphisms with atopic dermatitis in the Japanese population

Abstract: This study confirms the previous suggestion of an association between SPINK5 and AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
3
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(138 citation statements)
references
References 23 publications
4
122
3
9
Order By: Relevance
“…Interestingly, an insertion in the 3′ untranslated region of the kallikrein 7 gene (KLK7) encoding SCCE 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 35 has been reported to be associated with eczema. Early genome wide linkage analysis of eczema family studies suggested a potential locus on 5q31 and, after identification of 6 common polymorphisms in SPINK5, the variant Lys420Ser, was associated with eczema in a cohort of British children, 36 this association has been replicated in 2 small Japanese studies, 37,38 but other studies have failed to replicate this association. {REFS HERE} However, whereas FLG has been firmly established as a major gene for eczema, the reported effects of KLK7 and SPINK5 variants are rather weak and so far lack robust confirmation in replication cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, an insertion in the 3′ untranslated region of the kallikrein 7 gene (KLK7) encoding SCCE 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 35 has been reported to be associated with eczema. Early genome wide linkage analysis of eczema family studies suggested a potential locus on 5q31 and, after identification of 6 common polymorphisms in SPINK5, the variant Lys420Ser, was associated with eczema in a cohort of British children, 36 this association has been replicated in 2 small Japanese studies, 37,38 but other studies have failed to replicate this association. {REFS HERE} However, whereas FLG has been firmly established as a major gene for eczema, the reported effects of KLK7 and SPINK5 variants are rather weak and so far lack robust confirmation in replication cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…A Glu420Lys polymorphism variant in the SPINK5 gene, which encodes serine proteinase inhibitor, Kazal type 5, has shown significant association with AD in two independent cohorts (22). This gene is expressed in the outermost layers of the skin and has been implicated in Netherton disease, an autosomal recessive disorder characterized by ichthyosis and atopy.…”
Section: Figurementioning
confidence: 99%
“…A)) of the SPINK5 gene and AD in a Japanese population and found a positive association of 7 SPINK5 SNPs (except for 1156G > A) with AD. (64,65) In addition a study of Six SNPs rs17718511, rs17860502, KN0001820, rs60978485, rs17718737, and rs1422985 in the SPINK5 gene provides evidence for a significant interaction between the SPINK5 gene that may contribute to AD susceptibility among Korean. (68) …”
Section: -Spink5 and Lekti Genementioning
confidence: 99%
“…(62) Otherwise, a recent study was suggested that the E420K LEKTI variant is a risk factor for AD through an increase in the TSLP expression. (63) Subsequently, recent studies found a significant association between (1258G > A) SPINK5 polymorphism and AD in Japanese, (64,65) and in German. (66) In individuals affected by AD, a significant maternal over-transmission of the risk allele to their children was demonstrated Walley et al (67) Folster-Holset al, studied 8 SNPs in different regions of the SPINK5 gene, including 4 non-synonymous SNPs leading to an amino acid change (Asp106Asn (G316A), Asn368Ser (1103A > G) and Asp386Asn (1156G > A), and, Gly463Gly (A1389G), Val553Val (C1659T), Leu756Leu (C2358T) and Gly804Gly C2412T) and Glu 825Asp (C2475T)).…”
Section: -Spink5 and Lekti Genementioning
confidence: 99%